EDUKASI TEHNIK ASEPTIK SEDIAAN STERIL BAGI TENAGA KESEHATAN DI FASILITAS PELAYANAN KESEHATAN KABUPATEN SUMBA TIMUR NTT - Dewi Isadiartuti; Sugiyartono Sugiyartono; Retno Sari; Muh Agus S Rijal; Dini Retnowati (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
The Government through Permenkes 72/2016 on Pharmaceutical Services Standards in Hospitals has provided guidance on the regulation of pharmaceutical service standards. Pharmaceutical services in the field of management of sterile preparations is one aspect that receives attention, because it will affect the quality of services provided to sufferers. East Sumba Regency is one of the East Nusa Tenggara provinces located in Eastern Indonesia. East Sumba Regency has a large enough population but health workers in health care facilities have limitations in getting the latest information. To answer this condition, training was held in collaboration with IAI PC East Sumba. The aim of the training is to increase the knowledge and skills of aseptic techniques for sterile preparations for health workers in health care facilities so that the quality of health services can be improved. The training was given in the form of lectures consisting of compatibility and stability material for parenteral preparations and dispensing materials for sterile preparations followed by the practice of aseptic techniques for sterile preparations. The training activity was attended by 49 participants consisting of pharmacists, nurses, midwives and pharmaceutical technical personnel who worked in hospitals, health services, health centers, clinics, and pharmacies in Sumba (East, Central and West). From the results of the evaluation of the activity, it was known that the participants gained knowledge and increased knowledge about the basic principles of aseptic techniques and there was an increase in the participants' understanding of the material provided.abstrakPemerintah melalui Permenkes 72/2016 tentang Standar Pelayanan Kefarmasian di Rumah Sakit telah memberikan arahan mengenai pengaturan standar pelayanan kefarmasian. Pelayanan kefarmasian di bidang pengelolaan sediaan steril merupakan salah satu aspek yang mendapat perhatian, karena akan memengaruhi mutu pelayanan yang diberikan kepada penderita. Kabupaten Sumba Timur merupakan salah satu wilayah propinsi Nusa Tenggara Timur yang terletak di Indonesia Bagian Timur. Kabupaten Sumba Timur memiliki jumlah penduduk yang cukup besar akan tetapi tenaga kesehatan di fasilitas pelayanan kesehatan memiliki keterbatasan dalam mendapatkan informasi terbaru. Untuk menjawab kondisi tersebut diadakan pelatihan bekerjasama dengan IAI PC Sumba Timur. Tujuan pelatihan adalah untuk meningkatkan pengetahuan dan ketrampilan tehnik aseptik sediaan steril bagi tenaga kesehatan di fasilitas pelayanan kesehatan agar mutu pelayanan kesehatan dapat meningkat. Pelatihan diberikan dalam bentuk ceramah terdiri dari materi kompatibilitas dan stabilitas sediaan parenteral dan materi dispensing sediaan steril dilanjutkan dengan praktek tehnik aseptik sediaan steril. Kegiatan pelatihan diikuti 49 peserta yang terdiri dari apoteker, perawat, bidan dan tenaga teknis kefarmasian yang bekerja di Rumah Sakit, Dinas Kesehatan, Puskesmas, Klinik, dan Apotek sedaratan Sumba (Timur, Tengah, dan Barat). Dari hasil evaluasi kegiatan diketahui peserta mendapatkan penyegaran ilmu dan peningkatan wawasan tentang prinsip dasar tehnik aseptik dan terdapat peningkatan pemahaman peserta terhadap materi yang diberikan.